The Effect Of Brand Equity On Purchasing Decisions (Study at PT. X in 2025) - Nathania Rendyasti Cahyaningtyas; Anang Muftiadi; Zaenal Muttaqin (Indonesian Journal Economic Review (IJER), 2026)
The increasing competition in the gold jewelry industry encourages companies to establish strong brand equity to influence consumers’ purchasing decisions. PT. X has implemented various brand equity enhancement strategies through improving brand awareness, brand association, perceived quality, and brand loyalty. Therefore, it is important to examine the extent to which these factors are associated with consumers’ purchasing decisions. This study aims to analyze the effect of brand equity on the purchasing decisions of PT. X products in 2025. This research employed a quantitative cross-sectional survey design. Primary data were collected through a Likert-scale questionnaire distributed to 100 respondents who had purchased PT. X products in 2025 using a purposive sampling technique. The data were analyzed using descriptive statistics, classical assumption tests, simple linear regression, the coefficient of determination, and the t-test. The results indicate that both brand equity and purchasing decisions are categorized as high. Furthermore, brand equity has a positive and statistically significant relationship with all dimensions of purchasing decisions (brand choice, distribution channel selection, purchase quantity, purchase timing, and payment method selection), with coefficients of determination (R²) ranging from 10.9% to 21.4% (the highest variance explained being payment method selection at 21.4%). These findings suggest that brand equity plays a meaningful role in supporting consumers’ purchasing decisions. Accordingly, the company is recommended to continuously strengthen its brand equity to maintain competitiveness and support sustainable purchasing behavior.